Official Visit from Atlantis Press (Part of Springer Nature) - UiTM, Pejabat Timbalan Naib Canselor (Penyelidikan & Inovasi) (UiTM, 2024)
News and activities Office of Deputy Vice-Chancellor (Research & Innovation) Feb 2024.